Potential For Religious Tourism: Pasarehan Mbah Mas Moch. Saleh - Efendi, Irwan; Azalea, Randiga Febrian Murni; Putri, Intan Melani; Pratama, Angga Dwi (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
The spread of Islam in Banyuwangi has a long history that needs to be re-examined, there are many stories that have developed in society about several figures who played an important role in the spread of Islam in Banyuwangi, one of which is Mbah Mas Moh Saleh who is said to be known as a teacher of great scholars in East Java, and Mbah Mas Saleh who is also known as a spiritual advisor to the Banyuwangi regent at that time. The greatness of Mbah Mas Saleh is less well known among the wider community, only a few elderly people know the figure of Mbah Mas Saleh. Therefore, we are interested in raising the story of Mbah Mas Saleh who is said to have a great influence on the spread of Islam in Banyuwangi and East Java, by studying the relics of Mbah Mas Saleh which can be used as historical learning based on religious tourism. This study sees opportunities in the field of tourism. This study uses interview methods and qualitative methods with a historical approach. The data used comes from various secondary sources (literature studies).